Perbandingan Kebijakan Cuti Paternitas Perwujudan Kesetaraan Dalam Lingkup Ketenagakerjaan Antara Indonesia Dengan Singapura dan Filipina - Puspitarini, Nabilah (Media Hukum Indonesia (MHI), 2024)
Gender equality is a frequently raised issue in important discussions or meetings of policymakers. This is because gender equality is related to various aspects, especially in the field of employment. In general, countries in the Asian continent still uphold a patriarchal culture. This has an impact on the employment aspects in each country. Therefore, this study will examine the comparison of paternity leave policies in several Asian countries using a qualitative research method. Based on the analysis and assessment that has been carried out, the comparison of paternity leave policies between Indonesia, the Philippines, and Singapore states that among these two countries, Indonesia still does not have specific legal regulations regarding paternity leave. Indonesia also still needs to add the duration of paternity leave not only limited to 2 to 5 days compared to the other two countries. In addition, patriarchal culture and different leave policies for civil servants and private employees hinder the implementation of equal paternity leave policies.